(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Gum Arabic (GA), a natural, edible hydrocolloid obtained predominantly from Acacia senegal and Acacia seyal, is a highly branched heteropolysaccharide composed mainly of arabinose, galactose, rhamnose, glucuronic acid, and small proportions of protein. Its unique molecular architecture comprising arabinogalactan (AG), arabinogalactan protein (AGP), and glycoprotein (GP) fractions confers exceptional solubility, emulsification, film-forming capacity, and stability, which underpin its long-standing relevance in food, pharmaceutical, cosmetics, and industrial applications. Renewed scientific interest in GA is driven by its biodegradability, safety, and functional versatility, as well as its growing importance as a sustainable biomaterial. Recent advances have focused on modifying GA to enhance its physicochemical and functional properties. Chemical, physical, and enzymatic approaches including oxidation, cross-linking, esterification, graft-copolymerization, and nanoparticle functionalization have produced derivatives with improved rheological behavior, stability, and targeted performance. Modified GA has demonstrated significant potential in Nano chemistry as a stabilizer and reducing agent for metal nanoparticles, in drug delivery through pH-responsive hydrogels and polysaccharide drug conjugates, and in environmental technologies such as wastewater remediation and semiconductor development. In construction materials, GA acts as a natural binder that improves compressive strength, durability, and water resistance of stabilized earth blocks, offering a sustainable alternative to conventional stabilizers. Beyond industrial applications, GA provides notable health benefits. As a fermentable dietary fiber, it functions as a prebiotic, enhancing mineral absorption and supporting gut microbiota. Its antioxidant, anti-inflammatory, antimicrobial, and detoxification properties contribute to renal, cardiovascular, and gastrointestinal protection. Modified GA derivatives, including aldehyde-functionalized and cross-linked forms, have also shown promise for controlled drug release, tissue engineering, and biomedical therapeutics. This review synthesizes current knowledge on the composition, structural characteristics, physicochemical properties, and applications of GA, with emphasis on recent modification strategies that broaden its utility across scientific and industrial domains. The growing development of GA-based materials highlights its potential as a renewable, biocompatible platform for next-generation technological innovations.